23.1k views
0 votes
I need help for this problem!

-9(x + 6) = 18 ​

User Ziad Adnan
by
5.6k points

2 Answers

4 votes

Answer:

x = -8

Explanation:

1. Divide both sides of the equation by -9 to get (x+6) = -2

2. Now that are left with x+6 you can subtract (inverse operation) the 6 from both sides of the equation to get x = -8

Hope this helps

User Keybits
by
4.2k points
5 votes
Factor -9(x+6)

-9x - 54 = 18
+54 +54

-9x = 72
/-9x /-9x

The answer would be x = -8
User Pikapops
by
5.0k points